A valorização do desejo feminino como via de inclusão escolar da aluna grávida e puérpera : um estudo a partir da filosofia e psicanálise - Souza, Maria Cecilia de (2014)
Teenage pregnancy often occurs, especially among adolescents between 15 to 19 years old, from lower social-economic levels. This phenomenon has an impact on the education process of this group and often results in school evasion. Through an action-research, we approach the reality of a public primary school in the city of Vitória/ES in order to understand and intervene in the way some school subjects deal with the feelings involved in the occurrence of pregnancy among students. We found that the school community is not commonly concerned about the subjective impact of pregnancy, giving birth and puerperium. On the other hand, it became evident that there students go through numerous emotional experiences. These experiences influence the way in which they cross the perinatal period and have incisive impact on their school life. The school dropout is due to a combination of subjective and objective factors ranging from prejudice, difficulty dealing with the affections and the lack of assistance from government projects and policies for the retention of students in the perinatal period in the public educational system. With this study, we intend to point out the importance of building pedagogical practices attentive to the emotions of a pupil in the perinatal period and the need for state investments in support educational policies for the pregnant and postpartum student.